Gap Identification between Bootcamp Programs and Industrial Needs Utilizing Text Mining - Muhammad Arief Ardyansyah; Ignatius Luddy Indra Purnama (Universitas Atma Jaya Yogyakarta, 2025)
This paper aims to identify the gaps between the bootcamp program and industrial needs using text mining techniques. The case studies focus on bootcamp programs for full-stack laravel vue.js developers, and uiux designers. The data utilized includes curriculum or syllabi from the boot camps and industrial requirements gathered from online job portals, particularly job descriptions from Indeed.com. The analysis revealed a gap of 30% between the bootcamp curriculum and industrial needs for full-stack Laravel vue.js developer, and 20% between the bootcamp curriculum and industrial needs for uiux designer. Based on this identification, alternative solutions were proposed to enhance the curriculum or syllabus. The results of the usability test are OK level. It is indicated that satisfactory outcomes, suggesting that the proposed improvements could help make bootcamp programs more responsive to the evolving needs of the related industry.